RESPONDING TO THE CALLS TO ACTION: REFLECTIONS ON TEACHING MANDATORY INDIGENOUS EDUCATION TO TEACHER CANDIDATES IN ONTARIO - Watson, Kaitlyn; Currie-Paterson, Natalie (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 2019)
Drawing on reflexive conversations, we describe our experiences teaching a new mandatory course in Indigenous education at Western University in London, Ontario. By discussing the successes, challenges, and mistakes made while teaching this course, we hope to continue to decolonize our practice as settlers, PhD students, and educators with the goal of working towards reconciliation in education and society. RÉPONDRE AUX APPELS À L’ACTION : RÉFLEXIONS SUR L’ENSEIGNEMENT D’UN COURS OBLIGATOIRE EN ÉDUCATION AUTOCHTONE OFFERT AUX FUTURS ENSEIGNANTS EN ONTARIO S’appuyant sur des discussions réflexives, nous décrivons notre expérience d’enseignement d’un nouveau cours obligatoire portant sur l’éducation autochtone et offert à l’Université Western, en Ontario. En partageant les succès vécus, les défis rencontrés et les erreurs faites pendant l’enseignement de ce cours, nous espérons poursuivre la décolonisation de notre pratique en tant que colonisateurs, doctorants et éducateurs, dans le but de contribuer à la réconciliation dans le domaine de l’éducation et dans la société.